BIBLIOTECA INCUBATOR – UN CONCEPT MODERN SAU TRADIȚIONAL: DISCUȚII, PUNCTE DE VEDERE ALE ANGAJAȚILOR BM „B.P. HASDEU” - KULIKOVSKI, Conferențiar universitar , Lidia (BIBLIOPOLIS, 2020)
The libraries transform, reinvent their activities, innovate forms and methods of public relations, revitalizing offers. The library incubator is a new concept circulated in the professional literature based on the educational role of the library. The library incubator is an environment that encourages creativity, innovation, ideas and sharing / acquiring skills, an environment that provides opportunities for personal and professional development for everyone. Does the Municipal Library “B.P. Hasdeu” meets this concept? This article is about what at the librarians, writers and artists think about the library incubator. Here are answers sociological experiment organized by the Studies and Researches Department. The general conclusions are that BM is not entirely a Library incubator. It’s encouraging and promising that librarians have very correctly identified the components, elements of an incubator, known areas, segments for improvement and strengthening.